2020
DOI: 10.15302/j-fase-2019305
|View full text |Cite
|
Sign up to set email alerts
|

Embryo-mediated genome editing for accelerated genetic improvement of livestock

Abstract: Selecting beneficial DNA variants is the main goal of animal breeding. However, this process is inherently inefficient because each animal only carries a fraction of all desirable variants. Genome editing technology with its ability to directly introduce beneficial sequence variants offers new opportunities to modernize animal breeding by overcoming this biological limitation and accelerating genetic gains. To realize rapid genetic gain, precise edits need to be introduced into genomicallyselected embryos, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 95 publications
(104 reference statements)
0
30
0
Order By: Relevance
“…The ability to efficiently generate non-mosaic, homozygous founder animals is important for the production of genome edited livestock. The use of the CRISPR/Cas9 system has been reported across many livestock species 3 , but few reports have characterized its use in bovine embryos. In this study, using the CRISPR/Cas9 system, we identified gRNAs that resulted in high rates of mutation at target locations in two autosomes and the X chromosome in bovine embryos with an overall high efficiency (81-90%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to efficiently generate non-mosaic, homozygous founder animals is important for the production of genome edited livestock. The use of the CRISPR/Cas9 system has been reported across many livestock species 3 , but few reports have characterized its use in bovine embryos. In this study, using the CRISPR/Cas9 system, we identified gRNAs that resulted in high rates of mutation at target locations in two autosomes and the X chromosome in bovine embryos with an overall high efficiency (81-90%).…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of genome editing studies have been reported in bovine zygotes 3 , and indicate the frequent production of mosaic embryos. The frequency of mosaicism varies depending upon the type of site-directed nuclease used, the timing of editing relative to embryonic development, the form and efficiency of the targeting regents, the intrinsic properties of the target locus, and the method of delivery 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it would require back crossing over many years to catch up to the genetic merit of contemporaneous animals, which renders this process unsuitably slow for a timely adaptation. By contrast, genome editing can prove the causative relationship between a specific mutation and impact on phenotype, and provide the scope for rapid introgression -essentially within a single generation (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…However, SCNT cloning is generally inefficient, and production of viable calves can be highly variable 6 . An alternative approach for increasing the efficiency of producing genome edited livestock is through direct cytoplasmic injection (CPI) of in vitro fertilized embryos 7 . However, the use of standard embryo culture and gene KI techniques by using CPI often results in embryos displaying high levels of genetic mosaicism 8 .…”
Section: Introductionmentioning
confidence: 99%